A Modern Look at the Origin of the Universe - Odenwald, Sten F. (Zygon, 1990)
Abstract. In what follows, I review the modern theory of the origin of the universe as astronomers and physicists are coming to understand it during the last decades of the twentieth century. An unexpected discovery of this study is that the story of “cosmogenesis” cannot be completely told unless we understand the fundamental nature of matter, space, and time. In the context of modern cosmology space has become not only the bedrock (so to speak) of our physical existence, it may yield a fuller understanding of the universe itself.